Choosing Best Hashing Strategies and Hash Functions - Singh, Mahima (My University, 2009)
The most common use of hashing is in computing that one might expect hash functions is not well understood, and that choosing appropriate function should not be difficult. Recommendations are made for choosing hashing a strategy and hashing method and measuring its performance. hashing. The report tries to find out the advantages and disadvantages of hashing. It discusses about hashing and its various components which are involved in hashing and states the need of using hashing i.e. for faster data retrieval. The report contains the study of hash table and the problem like collision which occur in managing the hash table and its solution to overcome the problem like separate chaining and open addressing, the various methods involve in open addressing like linear probing ,quadratic probing and double It discusses the hash table, its basic operations and typical hash function operations and the problems for which hash tables are suitable and for which hash tables are not suitable. It contains the some common hashing methods like the division method, multiplication methods, folding method and other hashing method Midsquare, Addition, Digit Analysis which are used in different application of hashing. And finally compare all the methods and techniques, so we can conclude that which methods are best suitable for which kind of problems. It helps to finding the best hashing technique and hash function is best for that problem. A hash function can be defined as a function that compresses a large message into a fixed small size ‘message digest’. There are many hash function but the most widely use of them is in cryptographic applications. These cryptographic hash functions are based on the block ciphers This thesis presents a survey on different types of the hash functions, different types of hashing methods ,hashing strategies and structural weaknesses of them or the limitation of them that in which kind of problem they are suitable and for what they can’t be used. Here comparison of various hash table techniques provides a great help for finding out the best suitable hashing for any problem. For it some popular techniques: open addressing, coalescent chaining and separate chaining are discussed. And all these comparison provides the base for our problem that is choosing the best hashing strategies and hash function.
M.E.(Software Engineering)
Keywords: Hash Keys; Hash Functions